HDL (High-Density Lipoprotein) and ApoA-1 (Apolipoprotein A-1) Potentially Modulate Pancreatic α-Cell Glucagon Secretion - Mancuso, Elettra; Mannino, Gaia Chiara; Fuoco, Anastasia; Leo, Antonio; Citraro, Rita; Averta, Carolina; Spiga, Rosangela; Russo, Emilio; De Sarro, Giovambattista; Andreozzi, Francesco; Sesti, Giorgio (Arteriosclerosis, thrombosis, and vascular biology, 2020)
OBJECTIVE:Subjects with low levels of HDL (high-density lipoprotein) and ApoA-1 have increased risk to develop type 2 diabetes. HDL levels are an independent predictor of β-cell function and positively modulate it. Type 2 diabetes is characterized by defects in both β and α-cell function, but the effect of HDL and ApoA1 on α-cell function is unknown. APPROACH AND RESULTS:We observed a significant negative correlation (r=−0.422, P<0.0001) between HDL levels and fasting glucagon in a cohort of 132 Italian subjects. In a multivariable regression analysis including potential confounders such as age, sex, BMI, triglycerides, total cholesterol, fasting and 2-hour postload glucose, and fasting insulin, the association between HDL and fasting glucagon remained statistically significant (β=−0.318, P=0.006). CD1 mice treated with HDL or ApoA-1 for 3 consecutive days showed a 32% (P<0.001) and 23% (P<0.05) reduction, respectively, in glucagon levels following insulin-induced hypoglycemia, compared with controls. Treatment of pancreatic αTC1 clone 6 cells with HDL or ApoA-1 for 24 hours resulted in a significant reduction of glucagon expression (P<0.04) and secretion (P<0.01) after an hypoglycemic stimulus and increased Akt and FoxO1 (forkhead/winged helix box gene, group O-1) phosphorylation. Pretreatment with Akt inhibitor VIII, PI3K (phosphatidylinositol 3-kinase) inhibitor LY294002, and HDL receptor SCARB-1 (scavenger receptor class B type 1) inhibitor BLT-1 restored αTC1 cell response to low glucose levels. CONCLUSIONS:These results support the notion that HDL and ApoA-1 modulate glucagon expression and secretion by binding their cognate receptor SCARB-1, and activating the PI3K/Akt/FoxO1 signaling cascade in an in vitro α-cell model. Overall, these results raise the hypothesis that HDL and ApoA-1 may have a role in modulating glucagon secretion.